PENINGKATAN DATABASE SISTEM PENCATATAN AKUNTANSI DI SIMAK BMN BLU UNJ TENTANG KONSTELASI AMORTISASI PENGELOLAAN ASET TIDAK BERWUJUD - Petrolis Nusa Perdana (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
This Community Service activities are carried out using the substantive developing database approach to assertions - accounting management assertions of intangible assets recorded in the State - Owned Financial Management Information System (SIMAK BMN) of the Public Service Agency of Universitas Negeri Jakarta. The substantive developing database carried out includes assertions - occurrence assertions, completeness, valuation, right and obligation and disclosure. The results of the substantive developing will be used as follow-up material from the recommendations of the findings of the Republic of Indonesia Supreme Audit Agency to the Republic of Indonesia Ministry of Technology and Higher Education where the Public Service Agency of Universitas Negeri Jakarta is one of the entities that sampling BPK RI. The Community Service activity is also an alternative discussion to be a guideline for the existence of a research gap in the implementation of the PSAK (Statement of Financial Accounting Standards) Number 19 concerning intangible assets that adopt the basis of IFRS (International Financial Reporting Standards) where financial reports on assets become reliable, must be assessed based on fair value. PSAK 19 regulates the appraisal time to be carried out at the latest 3 years and at the latest every 5 years. This is where a phenomenon occurs, where if the appraisal is carried out in the 5th year while the amortization period of the intangible asset has been completed before 5 years, then the audit cannot be carried out based on the audit management assertions and make the asset the subject of audit findings potentially affecting audit opinion if material.Participants were given training on tips for managing a procurement of intangible fixed assets, both in the context of procurement by the university or by other units in certain circumstances, and systematically recording the SIMAK BMN UNJ after first carrying out asset reconciliation regular with the accounting and reporting section.